Sense of coherence’s impact on a level of depression patients diagnosed with colorectal cancer - Kurowska, Krystyna; Kubak, Anetta (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Introduction : Cancer for most people mean the death sentence. The SOC has a significant role in the experience of anxiety and stress. Person, who is able to use internal and external resources is better copping with the disease. Aim : Determine the influence of the sense of coherence on a degree of depression patients with colorectal cancer. Material and methods : We studied 92 patients treated at the Oncology Center in Bydgoszcz, using designed on our own survey, Antonovsky’s questionnaire of Guidance (SOC-29) and Beck’s depression scale. Results : Respondents had an average level of sense of coherence and a mild or moderate degree of depression. It has been shown a strong correlation between sense of coherence and depression. The higher level of SOC gives the lower level of depression, while a high level of depression was caused by low levels of SOC. There has been showed reduction of a global SOC in a group of people aged from 70 to 80. It may be connected with a fear of the consequences of the disease and fear of dependence on others. Conclusions : The results may affect the preparation for patient’s independent life with the disease. Show us the way of better care planning for the sick, and implement actions to aid in the acceptance of the disease.